A comprehensive review on the molecular dynamics simulation of the novel thermal properties of graphene. Issue 109 (20th October 2015) - Zhang, Jingchao; Xu, Fei; Hong, Yang; Xiong, Qingang; Pan, Jianming
Abstract : This review summarizes state-of-the-art progress in the molecular dynamics simulation of the novel thermal properties of graphene. Abstract : This review summarizes state-of-the-art progress in the molecular dynamics (MD) simulation of the novel thermal properties of graphene. The novel thermal properties of graphene, which include anisotropic thermal conductivity, decoupled phonon thermal transport, thermal rectification and tunable interfacial thermal conductance, have attracted enormous interest in the development of next-generation nano-devices. Molecular dynamics simulation is one of the main approaches in numerical simulation of the novel thermal properties of graphene. In this paper, the widely used potentials of MD for modeling the novel thermal properties of graphene are described first. Then MD simulations of anisotropic thermal conductivity, decoupled phonon thermal transport, thermal rectification and tunable interfacial thermal conductance are discussed. Finally, the paper concludes with highlights on both the current status and future directions of the MD simulation of the novel thermal properties of graphene.